2018
DOI: 10.1021/acsomega.8b02583
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Description of Mixed Film Formation at the Air/Water Interface: Carboxylic Acids–Alcohols

Abstract: The thermodynamic parameters of formation and clusterization of aliphatic alcohols C n H 2 n +1 OH and carboxylic acids C n H 2 n +1 COOH ( n = 6–16) are calculated using the quantum-chemical semiempirical PM3 method. Four types of dimers are constructed in two directions of the spread monolayer comprising the most energetically advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Figure shows that the dependences for clusterization Gbbs energy of mixed films are lower than the corresponding dependences for the individual components (except for the cases with X COOH = 80 and 90 mol %). This indicates a synergetic interaction between amine and acid hydrophilic parts unlike in the case considered in our previous study devoted to mixtures of aliphatic alcohols and carboxylic acids . In the last case, dependences of Δ G 298 Cl,∞ / m for mixed alcohol–acid films are between the lines of the corresponding dependences for pure monolayers.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Figure shows that the dependences for clusterization Gbbs energy of mixed films are lower than the corresponding dependences for the individual components (except for the cases with X COOH = 80 and 90 mol %). This indicates a synergetic interaction between amine and acid hydrophilic parts unlike in the case considered in our previous study devoted to mixtures of aliphatic alcohols and carboxylic acids . In the last case, dependences of Δ G 298 Cl,∞ / m for mixed alcohol–acid films are between the lines of the corresponding dependences for pure monolayers.…”
Section: Resultssupporting
confidence: 85%
“…This indicates a synergetic interaction between amine and acid hydrophilic parts unlike in the case considered in our previous study devoted to mixtures of aliphatic alcohols and carboxylic acids. 18 In the last case, dependences of ΔG 298 Cl,∞ /m for mixed alcohol−acid films are between the lines of the corresponding dependences for pure monolayers. This indicates the absence of synergetic action between alcohol and acid molecules.…”
Section: ■ Methods Of Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the immense diversity in sources from which atmospheric and oceanic organic molecules originate, mixed monolayer films are more suitable for the purpose of representing sea spray aerosol and the SSML. Experimental techniques and molecular dynamics simulations have both been used to study the interfacial properties of mixed monolayers at the air–water interface. ,, Surface properties of binary mixtures of fatty acids with other organic molecules such as amines, esters, cholesterols, and alcohols have received significant attention during the past two decades. ,, These studies have revealed substantial differences between the physical and chemical properties of a pure fatty acid monolayer and a mixed monolayer that contains fatty acid. The inclusion of a secondary surfactant in a fatty acid monolayer has been shown to alter film packing structure, thermodynamic behavior, and monolayer stability .…”
Section: Resultsmentioning
confidence: 99%
“…Experimental techniques and molecular dynamics simulations have both been used to study the interfacial properties of mixed monolayers at the air−water interface. 22,46,47 Surface properties of binary mixtures of fatty acids with other organic molecules such as amines, esters, cholesterols, and alcohols have received significant attention during the past two decades. 46,48,49 These studies have revealed substantial differences between the physical and chemical properties of a pure fatty acid monolayer and a mixed monolayer that contains fatty acid.…”
Section: ■ Results and Discussionmentioning
confidence: 99%